Penn State Worry Questionnaire – 10: A new tool for measurement-based care. (30th May 2016) - Yao, Beier; Sripada, Rebecca K.; Klumpp, Heide; Abelson, James L.; Muzik, Maria; Zhao, Zhuo; Rosenblum, Katherine; Briggs, Hedieh; Kaston, Michelle; Warren, Ricks
Abstract: The Penn State Worry Questionnaire – Past Week (PSWQ-PW) is an adaptation of the widely used Penn State Worry Questionnaire, measuring pathological worry weekly. However, it contains problematic negatively worded items and has not been validated in a large sample yet. To meet the needs of measurement-based care (MBC), we developed a shortened version (PSWQ-10) based on the PSWQ-PW, retaining only positively worded items, and examined its psychometric properties and clinical utility. Patients with Generalized Anxiety Disorder (GAD), Major Depressive Disorder (MDD), and other anxiety disorders completed the PSWQ-10 and other instruments during routine evaluation in an academic anxiety clinic. A second cohort from a perinatal clinic was evaluated similarly. The PSWQ-10 displayed excellent internal consistency, convergent and discriminant validity, and criterion group validity. Patients with GAD scored significantly higher than those with other anxiety disorders but did not differ from those with MDD. The PSWQ-10 showed sensitivity to change over time and demonstrated excellent psychometric properties in the perinatal population. The PSWQ-10 is a reliable, valid, efficient, and straightforward worry-focused instrument that can be readily used in MBC and help clinicians objectively measure worry as a treatment outcome in broad clinical populations. Highlights: Developed a short past-week version of the Penn State Worry Questionnaire (PSWQ-10). PSWQ-10 displays excellent internal consistency and good validity. PSWQ-10 shows sensitivity to change over time. PSWQ-10 shows excellent psychometric properties in a perinatal population.